Hubungan indeks massa tubuh (IMT) dengan kadar gula darah puasa pada siswa sekolah menengah atas (SMA) Negeri di wilayah Denpasar Utara - Astiti, Ari Puji; Dwipayana, Made Pande (E-Jurnal Medika Udayana; Vol 7 No 3 (2018): E-Jurnal Medika Udayana, 2018)
Obesity in adolescence is rising increasingly in number of events. Excess fat in individuals with obesity can cause insulin resistance which is a condition when insulin hormone ability to lower blood glucose is decrease. The aim of this study is to determine the relationship between body mass index with fasting blood glucose level in adolescence, especially in high school students. This study was cross-sectional study. The sample were 120 senior high school students who have been involved inclusion and exclusion criteria. And after that data will be analyze using Kendall’s tau. The result of this study showed 23 people were overweight, and 3 people obesity. Whereas for fasting blood glucose levels, 65 people normal fasting blood glucose, and 55 people have high fasting blood glucose. P value from Kendal’s tau was 0,121 (p<?) and showed there is no significant relationship between body mass index with fasting blood glucose levels. Keywords: Body Mass Index, (BMI), Fasting Blood Glucose Levels, Senior High School